A third-order non-local problem with boundary integral condition for a parabolic equation - Tarek, Bahloul; Mouhammed, Bouzit (International Journal of Applied Mathematical Research, 2015)
The present paper is devoted to a proof of the existence and Â uniqueness of a third-order non-local problem with boundary integral condition for a parabolic equation . The proof is based in two sided a priori estimates and the fact that the range of operator generalized by the considered problem is dense.
Keywords: Integral Boundary Condition; Energy Inequalities; nonlocal condition.